Assessing food availability in postglacial environments: Comparing assemblages from El Paso and Hoyada Verde formations, Pennsylvanian from Central Western argentinean basins - Halpern, Karen (2022)
The brachiopod and bivalve assemblages from coeval glacio-marine deposits of the Hoyada Verde and El Paso formations (late Serpukhovian–Bashkirian, Calingasta-Uspallata basin) have been thoroughly studied from taxonomic, biostratigraphic, and classical paleoecological views. Given their close geographical location, the marked compositional differences still raise some questions. Preliminary analysis suggests that it could be related to their bathymetrical preferences. Body size structure is highly sensitive to food availability and, therefore, an excellent study model for understanding the environmental context in which organisms developed. We hypothesize that a large influx of detritus in the water column sustains larger body sizes. This contribution aims to evaluate body size on local and regional scales. For that, 166 specimens were measured from articles previously published and the body size distribution was estimated using a geometric mean index by genus and an occurrences database. No significant differences between assemblages’ body size distributions were recognized, but bivalves seem to be smaller than brachiopods in Hoyada Verde, suggesting resource partitioning. From a stratigraphic point of view, both localities record an increase of body size in the lower part of the sections and then remain stable in the middle and upper parts. Minor variations detected along the sections could be indicating changes in food influx. On average, taxa in El Paso are smaller than in Hoyada Verde pointing to less food availability. Further, the dominance of detritivorous bivalves in El Paso also suggests oligotrophic conditions: brachiopods would intake from the water column while bivalves directly from the substrate.